The direction of word stress processing in German: evidence from a working memory paradigm - Domahs, Frank; Grande, Marion; Huber, Walter; Domahs, Ulrike (Frontiers in Psychology, 2014)
There are contradicting assumptions and findings on the direction of word stress processing in German. To resolve this question, we asked participants to read tri-syllabic nonwords and stress ambiguous words aloud. Additionally, they also performed a working memory task (2-back task). In nonword reading, participants’ individual working memory capacity was positively correlated with assignment of main stress to the antepenultimate syllable, which is most distant to the word’s right edge, while a (complementary) negative correlation was observed with assignment of stress to the ultimate syllable. There was no significant correlation between working memory capacity and stress assignment to the penultimate syllable, which has been claimed to be the default stress pattern in German. In reading stress ambiguous words a similar but non-significant pattern was observed as in nonword reading. In sum, our results provide first psycholinguistic evidence supporting leftward stress processing in German. Our results do not lend support to the assumption of penultimate default stress in German. A specification of the lemma model is proposed which seems able to reconcile our findings and apparently contradicting assumptions and evidence.